WOMEN ON BOARD AND FIRM PERFORMANCE: EVIDENCE FROM INDONESIA LQ45 - Valentine Siagian (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
This paper examines how the existence of women on board affect firm performance in Indonesia with a sample of Indonesia LQ 45. Women on board measured by (1) the percentage of female director and (2)the percentage of independent female director over a number of female directors. The result shows that the firms which have women on board have significant higher ROA and NPM, thus having women on board doesn’t significantly affect ROE. Moreover, firms having women on board as an independent director have significantly higher NPM. This result shows that it will not hurt the firm to have women on board, instead of having women on board statistically increase net profit margin in Indonesia LQ45.